Rasionalitas Orientasi Politik Masyarakat Nelayan Pada Pemilihan Umum Di Kabupaten Majene - Irwansyah Mansur; Gustiana Kambo; A. M. Rusli (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2019)
This study aims to determine and analyze the political orientation of the fishing communities in Majene Regency which is also associated with their rationality in voting in elections. This research was conducted in Majene Regency, West Sulawesi Province, using qualitative research type with descriptive type of analysis. Determination of informants was conducted purposively. Data was obtained through in-depth interviews and literature review. Data was analyzed using political orientation theory, rational choice theory, Coleman and other rationality concepts. The results showed that cognitive orientation, fishermen's knowledge of the general election was still very low. In making political decisions, they do not consider the program and vision and mission of the political parties but only consider the figures they know and like. In the affective orientation aspect, fishermen do not feel that the results of the previous elections can benefit their lives so that they will not consider the results of the party's performance. last election. This is due to the emergence of disappointment at the performance of political parties in the previous election. aspects of evaluative orientation, fishermen will still distribute their political rights in elections but their decisions are based on decisions for their comfort and security to live in rented land or loans from landlords who also direct fishermen to choose the candidate that the landlord wants. The decision to vote was also based on the rise of money politics by the candidates.